FNDC4 alleviates cardiac ischemia/reperfusion injury through facilitating HIF1α-dependent cardiomyocyte survival and angiogenesis in male mice - Xin Zhang; Yi-Peng Gao; Wen-Sheng Dong; Kang Li; Yu-Xin Hu; Yun-Jia Ye; Can Hu (Nature Communications)
Abstract Fibronectin type III domain-containing (FNDC) proteins play critical roles in cellular homeostasis and cardiac injury, and our recent findings define FNDC5 as a promising cardioprotectant against doxorubicin- and aging-related cardiac injury. FNDC4 displays a high homology with FNDC5; however, its role and mechanism in cardiac ischemia/reperfusion (I/R) injury remain elusive. Here, we show that cardiac and plasma FNDC4 levels are elevated during I/R injury in a hypoxia-inducible factor 1α (HIF1α)-dependent manner. Cardiac-specific FNDC4 overexpression facilitates, while cardiac-specific FNDC4 knockdown inhibits cardiomyocyte survival and angiogenesis in I/R-stressed hearts of male mice through regulating the proteasomal degradation of HIF1α. Interestingly, FNDC4 does not directly stimulate angiogenesis of endothelial cells, but increases the expression and secretion of fibroblast growth factor 1 from cardiomyocytes to enhance angiogenesis in a paracrine manner. Moreover, therapeutic administration of recombinant FNDC4 protein is sufficient to alleviate cardiac I/R injury in male mice, without resulting in significant side effects. In this work, we reveal that FNDC4 alleviates cardiac I/R injury through facilitating HIF1α-dependent cardiomyocyte survival and angiogenesis, and define FNDC4 as a promising predictive and therapeutic target of cardiac I/R injury.